Transcriptomic Signatures of Pearl Oyster Pinctada Maxima in Response to Acute Salinity Stress - Wei, Haijun; Chen, Mingqiang; Deng, Zhenghua; Sun, Jing; Yang, Jingru; Zhao, Wang; Li, Youning; Ma, Zhenhua; Wang, Yu; Yu, Gang (Frontiers in Marine Science, 2022)
Acute salinity stress can impact many physiological processes of marine shellfish. The responses of Pinctada maxima to salinity stress, especially the osmotic pressure regulation and immune response, is of great significance to health. To investigate the molecular changes in response to acute salinity stress, the pearl oysters were transferred from 30 ppt (C) to 40 ppt (HS) and 20 ppt (LS) for 12 h, and the transcriptome analysis was conducted on gills. Compared to the control, there were 6613 (3253 up-regulated and 3360 down-regulated) differentially expressed genes (DEGs), 4395 (2180 up-regulated and 2215 down-regulated) DEGs observed in HS and LS, respectively. The related molecular biological processes and potential functions were explored from enrichment analysis. A total of 332 KEGG pathways (including 1514 genes) and 308 KEGG pathways (including 731 genes) were enriched in C vs HS and C vs LS, respectively. In addition, there are 1559 DEGs shared by C vs HS group and C vs LS group, and the results of KEGG function annotation showed that 7 DEGs were involved in membrane transport, and 34 DEGs were involved in immune system. The correlation network for expression of genes shows that the expression of 3 genes were significantly correlated with each other in membrane transport, and there were there were significant correlations between the expression of 27 genes in immune response. The results of this study will be of great value in understanding the molecular basis of salinity stress adaptation in the pearl oyster P. maxima.